Neuroimaging Spectrum in COVID-19 Infection: A Single-Center Experience - Tiwari, Sarbesh; Garg, Pawan Kumar; Panda, Samhita; Gupta, Aanchal; Hegde, Adarsh; Kumar, Deepak; Khera, Daisy; Bhatia, Pradeep Kumar; Garg, Mayank; Yadav, Taruna (Indian Journal of Radiology and Imaging, 2023)
Background and Purpose The ongoing coronavirus disease 2019 (COVID-19) pandemic is a multisystemic disease and involvement of the nervous system is well established. The neurological and neuroimaging features of the disease have been extensively evaluated. Our study aimed to elucidate the neuroradiological findings in COVID-19 infected patients admitted to our institute during the first and second waves of the pandemic in India.Methods This was a single-center retrospective study of all COVID-19 positive patients who underwent neuroimaging between March 2020 and May 2021. The presenting neurological complaints, the imaging findings in computed tomography (CT) imaging, and/or magnetic resonance imaging (MRI) were recorded. They recorded the findings in the subheadings of ischemic stroke, hemorrhagic stroke, parainfectious demyelination, acute encephalitis syndrome, and changes of global hypoxic changes. Patients with age-related, chronic, and incidental findings were excluded.Results The study comprised of 180 COVID-19 positive patients who underwent neuroimaging. CT scan was performed for 169 patients, MRI for 28, and a combination of both CT and MRI was performed for 17 patients. Seventy percent of patients were males, and median age was 61.5 years (interquartile range: 48.25–70.75). Out of the 180 patients, 66 patients had nonspecific findings that could not be attributed to COVID-19 infection. In the remaining 114 patients, 77 (42.7%) had ischemic findings, while 22 (12.2%) had hemorrhagic stroke. Hypoxic ischemic changes were noted in five patients. The rest of the patients had a spectrum of changes including, cerebellitis (3), tumefactive demyelination (1), COVID-19-associated encephalitis (1), hemorrhagic acute demyelinating encephalomyelitis (1), transverse myelitis (1), cytotoxic lesions of corpus callosum (1), Guillain-Barre syndrome (1), and COVID-19-associated microhemorrhages (1).Conclusion Neurological manifestations of COVID-19 infection are not uncommon, and our understanding of this topic is expanding. A complex interplay of neurotropism and direct central nervous system invasion, immune activation and cytokine storm, vasculitis, and parainfectious processes are implicated in the pathophysiology. While the most common imaging finding was ischemic stroke, followed by hemorrhagic stroke, a diverse range of parainfectious findings was also noted in our study.
Keywords: cerebellitis; COVID-19; COVID-19-associated encephalitis; neuroimaging